Efficacy Evaluation of a Bivalent Vaccine Containing Porcine Circovirus Type 2b and Mycoplasma hyopneumoniae Against an Experimental Dual Challenge - Ahn, Yongjun; Yang, Siyeon; Oh, Taehwan; Park, Kee Hwan; Cho, Hyejean; Suh, Jeongmin; Chae, Chanhee (Frontiers in Veterinary Science, 2021)
The purpose of this study was to evaluate the efficacy of a new, single-dose bivalent vaccine containing porcine circovirus type 2b (PCV2b) and Mycoplasma hyopneumoniae against a dual PCV2b and M. hyopneumoniae challenge. At -25 days post challenge (dpc, 10 days of age), one pig group (designated as the vaccinated/challenged group) received a single, 1.0 mL dose of bivalent vaccine. Pigs in both the vaccinated/challenged and unvaccinated/challenged groups were then inoculated intranasally with PCV2b and M. hyopneumoniae at 0 dpc (35 days of age). Pigs in vaccinated/challenged group induced significantly higher levels of neutralizing antibodies against PCV2b and cell-mediated immunity against PCV2b and M. hyopneumonia when compared with pigs in unvaccinated/challenged group. The vaccination of pigs with a bivalent vaccine also reduced PCV2b viremia, reduced mycoplasmal nasal shedding, and decreased the severity of both lung and lymphoid lesions for PCV2b and M. hyopneumoniae infection, respectively. The results of this study demonstrated that the evaluated bivalent vaccine was effective in protecting pigs against PCV2b and M. hyopneumoniae infection.